Artists in Dylan Thomas's prose works : Adam naming and Aesop fabling - Mayer, Ann Elizabeth, 1960- (McGill-Queen's University Press, 1995)
Artists in Dylan Thomas's Prose Works is an exploration of the rich but relatively neglected prose works of Dylan Thomas. Ann Mayer examines the changing conceptions of language and the creation of meaning evident in Thomas's numerous self-referential acts of writing and telling. Through an analysis of the artist figures in Thomas's early experimental prose, Portrait of the Artist as a Young Dog, Adventures in the Skin Trade, and Under Milk Wood, Mayer shows how Thomas continually explored and reevaluated his vocation, the nature of his chosen medium, and the world itself. She links Thomas's prose works to his poetry through the blending of lyric and narrative strategies and examines Thomas's self-conscious concerns for his relationship to his modernist contemporaries. Mayer goes beyond the traditionally New Critical approaches that dominate Thomas scholarship, using contemporary critical theory to offer new insights into the complexity and ambiguity of a major twentieth-century writer.